Tired minds, normal scores: rethinking cognitive fatigue in multiple sclerosis - Spinetti, Davide; Zarbo, Ignazio Roberto (Frontiers in Neurology, 2025)
Cognitive fatigue is among the most pervasive and disabling symptoms experienced by individuals with multiple sclerosis (MS), yet it remains underrecognized and undertreated in both research and clinical settings. Despite its prevalence, cognitive fatigue is often confused with general fatigue or overlooked in standard neuropsychological assessments that rely on brief, decontextualized performance measures. This perspective argues for a paradigmatic shift in how cognitive fatigue is conceptualized and managed. This perspective define it as a core, dynamic dysfunction affecting the cognitive system’s capacity to sustain effort over time, distinct from both general and subjective fatigue. A growing body of evidence, highlighted in this article, shows a frequent dissociation between perceived fatigue and objective fatigability, underscoring a fundamental flaw in current assessment tools. The authors call for the integration of prolonged, dynamic, and ecologically valid measures, such as extended neuropsychological tasks and digital phenotyping, into clinical protocols. We propose repositioning cognitive fatigue as a distinct clinical target, requiring its own specific strategies for identification, monitoring, and intervention. Reframing cognitive fatigue in this way offers a critical step toward more accurate diagnostics and truly individualized care, bridging the gap between clinical findings and the patient’s lived experience.